2011
DOI: 10.1007/s10096-011-1310-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the clinical outcome of methicillin-resistant Staphylococcus aureus bacteraemia

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia is associated with high mortality due to a combination of host, pathogen and therapy related factors. This was a retrospective exploratory study to evaluate host, pathogen and therapy related factors influencing the clinical outcome of MRSA bacteraemia in a UK teaching hospital setting. Of the 38 consecutive episodes of MRSA bacteraemia over a 1-year period, 16 of 38 (40%) patients died at 1 month and 21/38 (55%) died at 6 months. Univariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…These data support the recent guidelines for vancomycin dosing [22] that recommend a trough serum concentration of !15 mg/L, supported by clinical data [48]. According to Monte Carlo simulation, this target is attainable only when the MIC of MRSA is 1 mg/L [23].…”
Section: Heteroresistancementioning
confidence: 82%
“…These data support the recent guidelines for vancomycin dosing [22] that recommend a trough serum concentration of !15 mg/L, supported by clinical data [48]. According to Monte Carlo simulation, this target is attainable only when the MIC of MRSA is 1 mg/L [23].…”
Section: Heteroresistancementioning
confidence: 82%
“…These include pathogen-specific factors such as SCCmec-associated virulence factors (3), with SCCmec type II being an independent predictor of mortality in a cohort study of 253 SAB (64% MRSA) (77) and 744 SAB (33% MRSA) (33) episodes. Alternatively, differences in empirical prescribing (243) and poor vancomycin efficacy (3,86,114) may explain some of these differences. Compared to semisynthetic penicillins, vancomycin has slower bactericidal activity in vitro, especially with high-inoculum infections (158,252), and variable tissue penetration (2,88,157).…”
Section: Methicillin Resistancementioning
confidence: 99%
“…However, reduced susceptibility to vancomycin in S. aureus isolates has been a major medical concern for more than a decade [6][7][8][9][10][11][12][13]. A number of studies have reported that elevated vancomycin minimum inhibitory concentrations (MICs) in MRSA isolates are associated with significantly higher mortality in the treatment of MRSA bacteraemia [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that elevated vancomycin minimum inhibitory concentrations (MICs) in MRSA isolates are associated with significantly higher mortality in the treatment of MRSA bacteraemia [8][9][10]. However, several recent reports showed no significant influence of MIC on the treatment outcome of patients infected with high-MIC isolates [11][12][13].…”
Section: Introductionmentioning
confidence: 99%